Comments about some species abundance patterns: classic, neutral, and niche partitioning models - Ferreira, F. C. [UNESP]; Petrere-Jr, M. [UNESP] (Int Inst Ecology, 2008)
The literature on species abundance models is extensive and a great deal of new and important contributions have been published in the last three decades. Broadly speaking, one can recognize five families of species abundance models: i) purely statistical or classic models (Broken-stick, Log-normal, Logarithmic and Geometric series); ii) branching process (Zipf-Mandelbrot and Fractal branching models); iii) population dynamics (Neutral models included); iv) spatial distribution of individuals (Multifractal and HEAP models) and v) niche partitioning (Sugihara's breakage and Tokeshi models). Among these the neutral, the classic and the niche partitioning models have been the most applied to natural communities, the former having been more extensively discussed than the others in the last years. The objective of this paper is to comment some aspects of the classic, neutral and niche partitioning models in a way that the proposed distributions may contribute to the analysis of the empirical patterns of species abundance. In spite of the variety of models, the distributions in general vary between the log-normal and the logarithmic series. From these models the Power-Fraction, together with independent niche dimensions measures, are amenable to experimental tests and may offer answers on which resources are important in the structuring of biological communities.
Keywords: species abundance patterns; neutral models; niche partitioning models; log-normal curve; Power fraction model